THE ETHNOMUSICOLOGY OF THE ILLE LE SONGS, MELOLO COMMUNITY, EAST SUMBA DISTRICT, EAST NUSA TENGGARA - Iswanto (Institut Agama Kristen Negeri Kupang, 2022)
Ethnomusicology is concerned with music and society. This research was conducted in Melolo, Umalulu District, East Sumba Regency. The problem in this study is how the ethnomusicology of the singing of Ille Le Melolo, East Sumba Regency, East Nusa Tenggara. The results of the research, the song Ille Le or the sleep songs for boys 'umbu', has unique characteristics in terms of musical form, poetry, and cultural meaning. Musically, this song consists of four notes, namely B, D#, E, and F. The intervals used are dominated by P1, M2, M3, P4, m2, M7, P5. An interval scheme like this will result in static movement and stepping with occasional interval jumps. The meter used is 68. When combined with the existing intervals, it will form a story song. The two lyrics of the song are very distinctive, this is related to the word 'umbu'. The word umbu is always in the lower notation in the musical structure of Ille Le's Song which is 185 Hz (F#3) and 240 Hz (B3). In addition, this song expresses the cultural meaning of the patriarchal system in East Sumba society. Musical structure cannot be separated from poetry. Ille le's ethnomusicological studies link the analysis of musical forms and poetry. Ethnomusicology includes musical characteristics such as the use of pentatonic scales, rhythm, motive, phrase, period and text interpretation.